Fast and efficient near-field to near-field and near-field to far-field transformation based on the spherical wave expansion - Boesman, B.; Pissoort, D.; Gielen, G.; Vandenbosch, G. A. E. (2015 IEEE International Symposium on Electromagnetic Compatibility (EMC), 2015)
This paper presents efficient methods to transform, interpolate and filter recorded near- and far-fields on spherical surfaces, based on a spectral decomposition of these fields in spherical harmonics. Combining a Fast Fourier Transform (FFT), Discrete Cosine Transform (DCT) and Discrete Sine Transform (DST) reduces the computation time of existing algorithms to a matter of seconds, even for densely sampled fields. Due to these fast run times, the proposed methods are very well suited for implementation in existing full-wave solvers and allow to only store the spectral decomposition of the fields. The latter heavily decreases necessary disk space, which is now indepedent from the chosen number of interpolation samples. Efficient and fast field visualisation tools have wide-spread applications in amongst others Electromagnetic Compatibility (EMC) diagnosis, education, and noise removal from gridded field data.